2013
DOI: 10.1128/jb.01021-13
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Full Genome of Helicobacter pylori Isolate Sahul64 Identifies Genes of High Divergence

Abstract: cIsolates of Helicobacter pylori can be classified phylogeographically. High genetic diversity and rapid microevolution are a hallmark of H. pylori genomes, a phenomenon that is proposed to play a functional role in persistence and colonization of diverse human populations. To provide further genomic evidence in the lineage of H. pylori and to further characterize diverse strains of this pathogen in different human populations, we report the finished genome sequence of Sahul64, an H. pylori strain isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 74 publications
2
29
0
Order By: Relevance
“…Such variation in size is due to inherent differences in (i) methodology (some used microarray and others used different gene prediction and ortholog clustering algorithms), (ii) the use of strict vs relaxed core genome definitions, and (iii) sample size/diversity (some were limited to only a few isolates or an individual strain lineage). Nonetheless, taken together these studies show C. difficile displays ultra-low levels of genome conservation, a trait rarely seen in bacteria and lower than other bacterial species considered to have high levels of genetic variability such as Campylobacter jejuni (59.2%), Helicobacter pylori (58.5%), Streptococcus pneumoniae (46.5%), and E. coli (~40.0%; Welch et al, 2002; Hiller et al, 2007; Lu et al, 2013; Vernikos et al, 2015). …”
Section: Discussionmentioning
confidence: 97%
“…Such variation in size is due to inherent differences in (i) methodology (some used microarray and others used different gene prediction and ortholog clustering algorithms), (ii) the use of strict vs relaxed core genome definitions, and (iii) sample size/diversity (some were limited to only a few isolates or an individual strain lineage). Nonetheless, taken together these studies show C. difficile displays ultra-low levels of genome conservation, a trait rarely seen in bacteria and lower than other bacterial species considered to have high levels of genetic variability such as Campylobacter jejuni (59.2%), Helicobacter pylori (58.5%), Streptococcus pneumoniae (46.5%), and E. coli (~40.0%; Welch et al, 2002; Hiller et al, 2007; Lu et al, 2013; Vernikos et al, 2015). …”
Section: Discussionmentioning
confidence: 97%
“…Using WGS, we and others detected potential mutations throughout the H. pylori genome and identified variants when sequence changes were present [20, 24, 25]. Here, we used WGS technology to detect novel variants in uncharacterized cag PAI genes associated with H. pylori pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Yahaghi et al (2014) 9 revealed that cagA (57.62%), vacA s1a (37.28%) and vacA m1a (30.50 %) had the highest prevalence among the H. pylori strains of vegetables. High prevalence of vacA genotypes among the clinical isolates and cases of gastrointestinal disorders have been reported from Iran, 22 United States, 23 Australia, 24 United Kingdom 25 and China. 26 Adjacent connotation of vacA genotypes with production of interleukin 8 (IL-8) and cytotoxins, adhesion to gastric epithelial cells, occurrence of inflammation, vacuolization, necrosis and apoptosis of epithelial cells has been reported in previously published data.…”
Section: Discussionmentioning
confidence: 99%